Perimenopause Exercises (Ergonomic Exercise) - Desi Br Sembiring; Serly Monika Br Sembiring; Ayu Jani Puspitasari (Sarana Ilmu Indonesia (salnesia), 2026)
Perimenopause is a transitional period before menopause characterized by hormonal changes and various physical and psychological complaints, such as sleep disturbances, hot flashes, fatigue, joint pain, and mood swings that can affect a woman's quality of life. One non-pharmacological effort that can be done to help reduce these complaints is through Ergonomic Exercise. This community service program aimed to provide health education and practical training on Ergonomic Exercise for perimenopausal women to improve their understanding of healthy lifestyle practices during the perimenopausal period. The activity was carried out on May 7, 2026 in Neighborhood III, Laucih Village, Medan Tuntungan District, Medan City, targeting 20 perimenopausal women selected using a total sampling technique. The activity methods included health education about perimenopause and the benefits of Ergonomic Exercise, movement demonstrations, hands-on practice, and discussion and question and answer sessions. The results of the activity showed that participants participated enthusiastically and actively during the education and exercise practice. Participants also showed an increased understanding of the importance of physical activity during perimenopause and the ability to practice Ergonomic Exercise movements independently. Ergonomic exercise was considered easy and safe and had the potential to help reduce physical complaints and provide relaxation among perimenopausal women. The activity demonstrated the potential to serve as a promotional and preventive effort to improve the health and quality of life of perimenopausal women through regular application of ergonomic gymnastics.